2017
DOI: 10.4103/jisppd.jisppd_280_16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of malocclusion severity and orthodontic treatment needs in 12–15-year-old school children of Namakkal District, Tamil Nadu, using Dental Aesthetic Index

Abstract: Malocclusion not only impacts the appearance of the person but also affects the self-esteem and psychological well-being. This is the first step in understanding the treatment need so that further steps can be taken in preventive and interceptive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…Only one Iraqi study of Kurdish people 20 and few studies of other populations have DAI analysis of malocclusion traits. 9,21,22 Also, because this study is the first study carried out for orthodontic patients who attend the orthodontic department so the results were completely different from previous Iraqi studies. Besides the differences in genetics and race, lead to differences from other populations.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Only one Iraqi study of Kurdish people 20 and few studies of other populations have DAI analysis of malocclusion traits. 9,21,22 Also, because this study is the first study carried out for orthodontic patients who attend the orthodontic department so the results were completely different from previous Iraqi studies. Besides the differences in genetics and race, lead to differences from other populations.…”
Section: Discussionmentioning
confidence: 72%
“…7 The Dental Aesthetic Index (DAI) is one of treatment need indices, developed by Cons et al (1986, USA), It has been adopted as a cross-cultural index by the World Health Organization (WHO), a number of researches revealed that the DAI is valid and reliable. 8,9 The index show single score which combine subjective, objective and clinical esthetic factors with a threshold limit (i.e. 31 or higher) to regularize with the needs for orthodontic treatment according to the severity of malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…A presença de oclusopatias neste estágio de desenvolvimento tem maior impacto na sociedade e no indivíduo em termos de qualidade de vida, desconforto, limitações sociais e funcionais, uma vez que o mesmo pode apresentar maiores difi culdades em ter contatos sociais, perder oportunidades na carreira e sentir-se constrangido com a sua aparência. Conforme Nagalakshm et al 16 e Sanadhya et al 18 , o tratamento precoce possui benefícios que englobam a prevenção, minimizando ou eliminando a necessidade de tratamento futuro mais complexo, correção da estética, melhora da função e da qualidade de vida.…”
Section: Discussionunclassified
“…4 These parameters can be measured from the study casts or by the intra-oral clinical examination. 5 The resulting score is categorized against the standardized values for the estimation of severity of malocclusion and treatment need requirements. 6 Malocclusion is defined as deviation from the normal characteristic of occlusion and dentofacial patterns, thus could affect the skeletal, dental or both the components.…”
Section: Introductionmentioning
confidence: 99%